The application of sale contract as a mechanism of ownership transfer in Islamic hire purchase - Muhammad Zin, Hakimah; Salamon, Hussin; Abdullah, Nurdianawati Irwani (Universiti Kebangsaan Malaysia, 2015)
Ownership transfer is significant in Islamic hire purchase (IHP) operation as it enables customers to own the asset at the end of lease (ijarah) contract. The ownership transfer in Islamic hire purchase transaction usually takes effect by executing a sale contract. The execution of sale contract in ownership transfer to be Shariah-compliant must comply with Shariah requirement otherwise it may leads to Shariah issue. The paper aims to investigate the extent to which the banks’ practices on the application of sale contract are in compliance with Shariah requirements. It examines Shariah requirements on the application of sale contract under Shariah legal framework and compares with banks’ actual practice. The study employs qualitative method of study comprised of document analysis by analyzing Shariah legal framework as well as documents of Islamic hire purchase facility of six financial institutions in Malaysia. The study found that the banks’ practices on the application of sale contract are in compliance with Shariah requirements whereby the sale contract is executed separately from the lease contract in a correct order and the transaction is proved in written documentation. However, there are different practices among these banks in terms of the sales contract documentation adopted. Therefore the paper suggests that a comprehensive guideline together with a standard sale contract document which is specifically applicable for ownership transfer in Islamic hire purchase transaction should be prepared. It is hope that the existence of such a comprehensive guideline on the sales contract documentation can enhance good governance and ensure sustainable development of Islamic finance.